2018
DOI: 10.1101/376764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting a Therapy-Resistant Cancer Cell State Using Masked Electrophiles as GPX4 Inhibitors

Abstract: We recently discovered that inhibition of the lipid peroxidase GPX4 can selectively kill cancer cells in a therapy-resistant state through induction of ferroptosis. Although GPX4 lacks a conventional druggable pocket, covalent small-molecule inhibitors are able to overcome this challenge by reacting with the GPX4 catalytic selenocysteine residue to eliminate enzymatic activity. Unfortunately, all currently-reported GPX4 inhibitors achieve their activity through reactive chloroacetamide groups. We demonstrate t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 75 publications
(87 reference statements)
2
34
0
Order By: Relevance
“…We employed two approaches to rule out potential POR-dependent ML210/RSL3 processing events. First, we synthesized alkyne analogs of ML210 and RSL3 -namely ML210-yne (3) and RSL3-yne (4) 15 , both of which preserved their ferroptosis-inducing activities in a POR-dependent manner (Figs. 3a-b, Supplementary Fig.…”
Section: Por Depletion Does Not Alter Gpx4-ml210/rsl3 Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed two approaches to rule out potential POR-dependent ML210/RSL3 processing events. First, we synthesized alkyne analogs of ML210 and RSL3 -namely ML210-yne (3) and RSL3-yne (4) 15 , both of which preserved their ferroptosis-inducing activities in a POR-dependent manner (Figs. 3a-b, Supplementary Fig.…”
Section: Por Depletion Does Not Alter Gpx4-ml210/rsl3 Bindingmentioning
confidence: 99%
“…Distinct from other GPXs, GPX4 is the only enzyme identified thus far that acts on phospholipid hydroperoxides 6,13 . Hence, inhibitors of GPX4, including ML210, ML162 and 1S,3R-RSL3 (RSL3), are used as specific inducers of ferroptosis in cells with high levels of polyunsaturated lipids -lipids that are highly susceptible to oxidation 1,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that the chloroacetamide group cannot be replaced with other less-reactive electrophiles (2-9). These include α-chlorofluoroacetamide (2), other haloacetamides (3)(4)(5)(6), and acrylamide (7). However, we observed that the propiolamide analog 8 exhibited potent ferroptosis induction with improved selectivity compared to ML162.…”
mentioning
confidence: 75%
“…[1][2][3] Induction of ferroptosis via inhibition of GPX4 has promising therapeutic potential, especially for targeting cancer cells that are otherwise therapy resistant. [4][5][6] However, GPX4 represents a difficult-to-drug target because it has a shallow active site that is not amenable to interacting with small molecules. 7,8 This topology constitutes a unique feature among the broader family of glutathione peroxidases, enabling reduction of structurally-diverse lipid hydroperoxide substrates.…”
mentioning
confidence: 99%
“…This has driven significant interest in the development of treatments to induce ferroptosis in cancer cells. Small molecule inhibitors of GPX4 have been developed and tested, but they are toxic and lack specificity (15), which limits in vivo use and clinical relevance.…”
Section: Introductionmentioning
confidence: 99%